General Volmar Anton von Shlippenbah – a Descendant of Livonian Knights - A. V. Bespalov; N. A. Kopylov (Vestnik MGIMO-Universiteta)
The article restores, on a basis of unpublished documents and little–known works, the biography of Volmar Anton von Shlippenbah, one of the participants in the Northern war (1700–1721), who battled on the side of the Swedish king for the long time and finished the career on the service of the Russian Empire.